Quantifying the Herd: Social Media Sentiment, Leverage, and Bitcoin Market Volatility - Yuan Tom, Liu Hong; Wang, Ruilin; Wang, Hairui; Cao, Ziqi; Yang, Chenglin (Theoretical and Practical Research in Economic Fields, 2026)
This study examines the impact of social media sentiment on Bit-coin market volatility. While existing literature often relies on single-source data or isolated factors, this research introduces a novel three-source pricing framework that integrates Twitter-derived social media sentiment, investor leverage ratios, and historical market data. Using a Weighted Least Squares (WLS) regression model to address heteroscedasticity in financial time series, we analyze daily Bitcoin returns from 2021 to the first half of 2022. Our results indicate that both social media sentiment has a statistically significant positive effect on Bitcoin returns. The model successfully identified high-risk market conditions, as validated by the May-June 2021 crash. These findings demonstrate that social media sentiment has a huge impact on cryptocurrency markets.